Spherical detector device mathematical modeling with taking into account detector module symmetry - Batiy, V.G.; Fedorchenko, D.V.; Prokhorets, I.M.; Prokhorets, S.I.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2005)
Mathematical model for spherical detector device accounting to symmetry properties is considered. Exact algorithm for simulation of measurements procedure with multiple radiation sources developed. Modelling results are shown to have perfect agreement with calibration measurements Розглянуто математичне моделювання шарового детектора з урахуванням властивостей симетрії. Представлено послідовний алгоритм моделювання процедури вимірювань за наявності декількох джерел випромінювання. Показано, що результати моделювання добре узгоджуються з калібрувальними вимірюваннями. Рассмотрено математическое моделирование шарового детектора с учетом свойств симметрии. Представлен последовательный алгоритм моделирования процедуры измерения при наличии нескольких источников излучения. Показано, что результаты моделирования имеют хорошее согласие с калибровочными измерениями.